Macroeconomic theory - Jhingan M. L (Delhi : Konark Publishers, 1986)
This is a revised and enlarged edition of the introductory microeconomics textbook designed primarily for B.A., B.Com (Pass and Hons) courses in Indian Universities. It deals with the neo-classical price theory in a simple, coherent and critical manner.
oif 16/04/2019
Loans
Keywords: Microecomics